ِعہد رسالت اور عہد خلافت میں جنگی قیدی-نبوی حکمت عملی کا تحقیقی مطالعہ - ڈاکٹر ارشد قبال, (Seerat Studies, 2024)
In ancient ages, there were generally two types of slavery; the first shape was that status wise weak person was made prisoner by the stronger people and after that he was made a slave and was sold out. The second shape of slavery was of war prisoners. Islam forbade the former shape and banned forever. However, the option of second shape was kept open. Before the emergence of Islam, the prisoners of war were treated tyrently. There was no option for them except being killed or permanent slavery. But Islam, the religion of mercy fixed rights of even slaves. Laws were made to mension their social status and different options were offered for their freedom. In this article, the study of Islamic laws and rules about slavery are presented and it has been proved in the light of Quran, Seerah and act of sacred companions that the objections of orientalists on Islamic laws regarding war prisoners are based just upon prejudice. Whereas Islamic law is quite moderate, balanced and actable.